The Marlowe-Shakespeare continuum : Christopher Marlowe, Thomas Nashe, and the authorship of early Shakespeare and anonymous plays. - Murphy, Donna N. (Cambridge Scholars Publishing, 2013)
In The Marlowe-Shakespeare Continuum, Donna N. Murphy demonstrates how Christopher Marlowe, sometimes in co-authorship with humorist Thomas Nashe, appears to have ""become"" Shakespeare on a linguistic basis. She documents a sharp, upward learning curve, with the initial penning of works she examines in the following chronological order: Caesar's Revenge, II Henry VI, The Taming of a Shrew, III Henry VI, Edward III, Titus Andronicus, Thomas of Woodstock, Romeo and Juliet, and I Henry IV, and se ...